National Rural Livelihood Mission and Women Empowerment in Nagaland : An Approach Based Village Study - M., Giribabu (Arthshastra Indian Journal of Economics & Research, 2022)
Indian society is patriarchal in nature and always tried to suppress and subordinate women in different facets of literature, social norms, and in other religious & mythological texts. The introduction of self-help groups in India was considered one of the most significant tools to adopt a participatory approach for women’s empowerment. The data for this study were collected from 300 respondents covering three intensive blocks under three districts of Kohima, Dimapur, and Mokokchung of Nagaland. The evidence showed that significant changes occurred in terms of socioeconomic and political empowerment after implementing the rural livelihood mission in all selected villages. The study’s findings revealed that about 73% of the respondents had attained economic security through decent work conditions, and 50.7% of the respondents stated that they attained more employment days in agricultural and other skilled employment activities under the NSRLM scheme. The study results disclosed that the quality of life and status of socioeconomic conditions improved significantly. However, distribution of property rights, participation in political activities, and freedom of movement by the women were limited in all selected villages, which need more strategies and training for women so that they are empowered in these areas.